2006
DOI: 10.1002/pbc.20757
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of complications in severe neutropenic children with cancer in the unprotected environment of an overnight camp

Abstract: Our results support the safety and feasibility of severely neutropenic patients with cancer to attend the non-isolated, non-sterile environment of a summer camp. These findings may be applicable to school and other social settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
4
3
0
Order By: Relevance
“…School attendance did not appear to be a risk factor for start of antimicrobial treatment due to infection, a finding consistent with one of the few studies that have investigated the relation between social interaction and the risk of acquiring an infection among children with cancer (Tabori, Jones et al 2007). In accordance with other reports (Bodey 1986;Auletta, O'Riordan et al 1999;Klaassen, Goodman et al 2000;Haupt, Romanengo et al 2001;Christensen, Nielsen et al 2005;Nam, Kim et al 2010), we identified neutropenia, certain diagnoses (sarcoma, NHL and AML) and type of treatment (chemotherapy combined with surgery) as factors related to the start of antimicrobial treatment.…”
Section: During Initial Cancer Treatmentsupporting
confidence: 81%
“…School attendance did not appear to be a risk factor for start of antimicrobial treatment due to infection, a finding consistent with one of the few studies that have investigated the relation between social interaction and the risk of acquiring an infection among children with cancer (Tabori, Jones et al 2007). In accordance with other reports (Bodey 1986;Auletta, O'Riordan et al 1999;Klaassen, Goodman et al 2000;Haupt, Romanengo et al 2001;Christensen, Nielsen et al 2005;Nam, Kim et al 2010), we identified neutropenia, certain diagnoses (sarcoma, NHL and AML) and type of treatment (chemotherapy combined with surgery) as factors related to the start of antimicrobial treatment.…”
Section: During Initial Cancer Treatmentsupporting
confidence: 81%
“…These results could assist health care professionals and parents in decision making about school attendance. Our results are consistent with those from one retrospective study that investigated the association between social interaction and infection in children with cancer who were either severely neutropenic or at a highintensity phase of chemotherapy [12].…”
Section: Discussionsupporting
confidence: 90%
“…Kinsella et al found that the majority of attendances for medical care at camp were for pain or injury. Whereas, Tabori et al reported that 9 (24%) of the campers needed hospitalization for fever and neutropenia, but no campers reported any bleeding episodes.…”
Section: Resultsmentioning
confidence: 97%
“…The literature search returned a total of 581 titles. Abstracts for all 581 articles were reviewed for inclusion and 20 met the inclusion criteria . Reference lists for each of the 20 articles included were also searched to ensure no relevant articles had been missed during the search strategy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation